Emergency department interpretation of CT of the brain: a systematic review. Issue 1102 (23rd December 2016) - Evans, Lachlan R; Fitzgerald, Mark C; Mitra, Biswadev; Varma, Dinesh
ABSTRACT: Background and objectives: CT of the brain (CTB) is one of the most common radiological investigations performed in the emergency department (ED). Emergency clinicians rely upon this imaging modality to aid diagnosis and guide management. However, their capacity to accurately interpret CTB is unclear. This systematic review aims to determine this capacity and identify the potential need for interventions directed towards improving the ability of emergency clinicians in this important area. Methods: A systematic review of the literature was conducted without date restrictions. We searched MEDLINE, EMBASE and Cochrane databases and studies reporting the primary outcome of concordance of CTB interpretation between a non-radiologist and a radiology specialist were identified. Studies were assessed for heterogeneity and a subgroup analysis of pooled data based on medical specialty was carried out to specifically identify the concordance of ED clinicians. The quality of evidence was assessed using the GRADE criteria. Results: There were 21 studies included in this review. Among the included studies, 12 reported on the concordance of emergency clinicians, 5 reported on radiology trainees and 4 on surgeons. Clinical and statistical heterogeneity between studies was high (I 2 =97.8%, p<0.01). The concordance in the emergency subgroup was the lowest among all subgroups with a range of 0.63–0.95 and a clinically significant error rate ranging from 0.02 to 0.24. Conclusions: Heterogeneity and the presence of bias limit our confidence in these findings. However, the variance in the interpretation of CTB between emergency clinicians and radiologists suggests that interventions towards improving accuracy may be useful.